Lawyers in Opera: The Transformation of the Legal Profession - Høedt-Rasmussen, Inger; Nielsen, Lise-Lotte (NAVEIÑ REET: Nordic Journal of Law and Social Research, 2015)
For centuries lawyers, broadly understood as judges, notaries, legal officials and private practicing lawyers, have played important roles in society and been members of a strong profession possessing privileges. Also in operas, from the Italian Commedia dell’arte, ‘Il dottore’, to recent lawyer figures, judges, notaries, lawyers, courtrooms, prisons and legal cultures are exposed. These conditions have influenced the reputation of lawyers. This article contributes with reflections about lawyers’ identity through a fruitful inspiring collaboration between an opera singer and a legal scholar. At three levels of analysis, this explorative study searches for connections between societal requirements (what to do), professional requirements (how to act) and legal and ethical expectations of specific lawyer-like behaviour, morality and good citizenship (who to be). The article brings into a dialogue the world of law and the world of opera and compares the construction of lawyer identities in society with different lawyer roles in opera.